Statistical Analysis and Optimization of Ammonia Nitrogen Removal from Aqueous Solutions and Landfill Leachate by Ultrasound Iradiation - Tobalt, Andrew (Université d'Ottawa / University of Ottawa, 2017)
The application of Ultrasound (US) irradiation to remove ammonia nitrogen from aqueous solutions, including synthetic solution and landfill leachate, at 20 kHz was investigated in this thesis. Batch experiments were carried out using two synthetic solutions with initial ammonia concentrations of 3000 and 5000 mg TAN/L in addition to two leachates from new and old landfills. The results of testing showed that US irradiation is an effective treatment technology for the removal of aqueous ammonia. More specifically, it was found that increasing sonication time and pH increased ammonia removal. The maximum observed removal of ammonia was 87.4% at a pH of 11 and sonication time of 25 minutes. Also, it was found that volatilization of ammonia to the atmosphere accounted for 0-7% of removal, the thermal effect of US accounted for 21.1-52.7%, and the non-thermal effect of US accounted for 44.5-78.8% (depending on pH and sonication time). Results of factorial design and response surface methodology showed that pH, energy output (kJ), and the interaction between the two were significant parameters. The predicted two factor interaction (2FI) model was in close agreement to the observed data (R2 = 0.94) and produced an optimum ammonia removal of 87% at a pH of 10.9 and energy output of 94.8 kJ. Analysis of variance tests showed that there were no significant differences in the percent removal of ammonia due to the non-thermal effects of US across all four solutions (synthetic and leachate) indicating that US irradiation is a non-selective treatment method for ammonia removal.
Keywords: Ultrasonic Irradiation; Ammonia; Statistical Analysis; pH; Sonication Time; Response Surface Methodology; Optimization; Factorial Design